Motivation and Employee Performance in Local Governments: A Case Study of Kanungu District Local Government Headquarters. - Kukunda, Right (Kabale University., 2024)
The purpose of this study was to unveil the role of motivation on employee performance and service provision in Kanungu District Local Government Headquarters. The study adopted a case study design using a quantitative research approach, Forty (40) respondents were selected for the study using a purposive sampling method. The respondents selected were from the various departments of Kanungu District Local Government Headquarters. The research results revealed that the motivation tools in use in Kanungu District Local Government Headquarters are salary and benefits, rewards and motivation, opportunities for growth and development, job security, supportive work environment, valuable feedback, appraisal, and appreciation. Most of the respondents (55%) strongly agreed that their work performance meets the organization's expectations. 63% of the respondents also strongly agreed that there was a link between their performance and the success of Kanungu District Local Government Headquarters. In trying to test the relationship between motivation and employee performance, 85% of the respondents strongly agreed that motivated employees perform better while 7% were neutral about this. 80% of the respondents also strongly agreed that there is a relationship between motivation and employee performance. The study summarized that the success of Kanungu District Local Government Headquarters was a result of employee motivation.